Effects of salting duration and salt concentration on physicochemical properties and sensory attributes of buffalo meatballs - Omar, Umi Afiqah; Kumar, Pavan; Ab Aziz, Muhamad Faris; Sazili, Awis Qurni; Ismail-Fitry, Mohammad Rashedi (Emerald Publishing, 2024)
Purpose: This paper aims to evaluate the effects of salting duration and salt concentration on the physicochemical, colour, texture and sensory attributes of buffalo meatballs. Design/methodology/approach: Minced buffalo meat was mixed with salt at 1 or 2% concentration and stored for 0 h, 24 h or 48 h during the preparation of meatballs. The developed meatballs were analysed for moisture content, water holding capacity (WHC), pH, cooking yield, shrinkage, colour, texture profile analysis, gelling properties and sensory attributes. Findings: The salting durations of 24 and 48 h had significant (p < 0.05) effects on the WHC and colour attributes of the buffalo meatballs. A 2% salt addition in meatballs significantly (p < 0.05) affected pH and cooking yield. Salting for 24 h with 2% salt concentration significantly (p < 0.05) increased the hardness, chewiness and gel strength of the meatballs. Thus, salting for 24 h with a 2% salt concentration improved the physicochemical, textural and sensory attributes of buffalo meatballs. Practical implications: The study highlighted the importance of salting treatment during the preparation of meat products. For example, salting buffalo meatballs with a 2% salt concentration for 24 h could improve their functional and sensory attributes. Originality/value: Studies on salting durations at different salt concentrations in buffalo meat are very limited. An optimized combination of salting duration and salt concentration during the preparation of buffalo meatballs could improve the quality attributes and acceptability of these products.